2003
DOI: 10.1080/02841860310017676
|View full text |Cite
|
Sign up to set email alerts
|

Proton Beams to Replace Photon Beams in Radical Dose Treatments

Abstract: With proton beam radiation therapy a smaller volume of normal tissues is irradiated at high dose levels for most anatomic sites than is feasible with any photon technique. This is due to the Laws of Physics, which determine the absorption of energy from photons and protons. In other words, the dose from a photon beam decreases exponentially with depth in the irradiated material. In contrast, protons have a finite range and that range is energy dependent. Accordingly, by appropriate distribution of proton energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 14 publications
0
65
0
1
Order By: Relevance
“…It has also been shown that the dose distributions in target volumes in the head and neck region can be improved by photon IMRT compared with conventional treatment (4 Á/6). Compared with photon IMRT, protons have an even greater capacity to deliver highly conformal dose distributions but with minimal integral doses (29,30). Treatment planning studies have also shown that protons offer an advantage compared with IMRT in some head and neck tumours (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the dose distributions in target volumes in the head and neck region can be improved by photon IMRT compared with conventional treatment (4 Á/6). Compared with photon IMRT, protons have an even greater capacity to deliver highly conformal dose distributions but with minimal integral doses (29,30). Treatment planning studies have also shown that protons offer an advantage compared with IMRT in some head and neck tumours (31).…”
Section: Discussionmentioning
confidence: 99%
“…I must admit that there are good physical arguments in favour of protons [19,20]. On the other hand, much better results than current results may emerge from IMRT and not the least from better diagnostic procedures disclosing the biological properties of a tumour and selection of areas where appropriate radiation can selectively be deposited as mentioned above.…”
Section: Olav Dahlmentioning
confidence: 99%
“…For many types of tumors, this has led to unacceptably low tumor control probability (TCP) and to high levels of morbidity. An alternative approach involves the use of protons and other heavier ions [1][2][3][4]. As R. R. Wilson pointed out in 1946 [5], for these charged particles both the amount and rate of energy deposition increase dramatically as the particle nears the end of its range.…”
Section: Introductionmentioning
confidence: 99%